APPLICATION OF THE PROBLEM BASED LEARNING MODEL ASSISTED WITH LEARNING VIDEOS TO IMPROVE MATHEMATICS LEARNING OUTCOMES FOR CLASS IX SMP - Sukarim; Nurmala, Santi; Ferdianto, Ferry (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2024)
The aim of this research is to determine the students stay focused and alert in various learning situations that are occurring so that there is an increase in the completeness of learning outcomes. Keywords— Problem based learning; learning videos; learning outcomes. implementation of the problem based learning model assisted by learning videos in improving student learning outcomes in each cycle, as well as to determine the learning motivation of students in class IX SMPN 1 Sukagumiwang. The research method used is Classroom Action Research (PTK). The research was carried out in three cycles, each cycle consisting of planning, implementing actions, observing and reflecting. The subjects of this research were 20 students in class IX of SMPN 1 Sukagumiwang. The data collection used in this research is qualitative and quantitative data. Qualitative data in the form of observation sheets on the implementation of the problem based learning model and student motivation questionnaire sheets. Meanwhile, the quantitative data is that students' learning results in the transformation material for each cycle have increased above the KKM value, namely 73, after implementing the problem-based learning model assisted by learning videos. Student learning outcomes in cycle I were 65% with an increase in N-gain learning outcomes of 92 (very good). Student learning outcomes in cycle II were 85% with an increase in N-gain learning outcomes of 95 (very good). This shows an increase from cycles I and II, 3) students' learning motivation through the application of the problem based learning model assisted by learning videos on reflection and rotation transformation with an average score of 75% in the very good category. The application of the problem based learning model assisted by learning videos can increase students' activeness in learning, and can help students stay focused and alert in various learning situations that are occurring so that there is an increase in the completeness of learning outcomes.